Adoption of Agile Approach in Developing Fleet Management System for Cargo Companies - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This research investigates adopting Agile methodology in developing fleet management systems for cargo companies. The problem investigated is how using Agile methodology can improve the efficiency and effectiveness of Fleet Management System development and response to changes in the dynamic cargo industry. The research method involved a comprehensive literature review, interviews with cargo industry experts and Agile experts, a survey of potential users of the Fleet Management System, and functional testing and User Acceptance Test (UAT) of the developed system. The results showed that adopting the Agile methodology successfully resulted in a responsive and adaptive Fleet Management System with an intuitive user interface, good vehicle management functionality, accurate shipment tracking, and optimized system performance. This research contributes to providing a more in-depth view of the benefits and implications of using Agile methodology in Fleet Management System development for the cargo industry, as well as providing solutions that can improve operational efficiency and services for cargo companies and end users.